2014
DOI: 10.2355/isijinternational.54.1266
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Evaluations of REM Clusters in Stainless Steel

Abstract: It is known that clusters in liquid steel have a harmful effect on the casting process and the quality of the final steel product. In this study, clusters of rare earth metals (REM) were investigated in steel samples of a S30185 stainless steel grade from a pilot trial (PT, 250 kg) and from an industrial heat (IH, 100 t). Samples were taken from the liquid steel at different holding times after the addition of mischmetal. Thereafter, REM clusters collected on film filters after electrolytic extraction and filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
(23 reference statements)
0
28
0
Order By: Relevance
“…The three-dimensional morphology of REE clusters in the 20 wt%Cr(-11wt%Ni) steels was recently reported by Karasev and Jonsson's research group using electrolytic extraction method. 19,20) From pilot scale casting practice of REE treated 20wt%Cr-10wt%Ni steels, they found that small single inclusions, probably formed due to steel reoxidation, resulted in faster clogging than large clusters did. 21) Recently, we investigated the effect of Al deoxidation on the inclusion evolution process in Ce-containing ASS melts.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional morphology of REE clusters in the 20 wt%Cr(-11wt%Ni) steels was recently reported by Karasev and Jonsson's research group using electrolytic extraction method. 19,20) From pilot scale casting practice of REE treated 20wt%Cr-10wt%Ni steels, they found that small single inclusions, probably formed due to steel reoxidation, resulted in faster clogging than large clusters did. 21) Recently, we investigated the effect of Al deoxidation on the inclusion evolution process in Ce-containing ASS melts.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth (RE)‐containing inclusions is one of the optimal inclusions for developing AF microstructures. However, the RE‐bearing inclusions tend to form clusters and remain in molten steel as large inclusions, which are harmful to the mechanical properties of steel …”
Section: Introductionmentioning
confidence: 99%
“…However, the RE-bearing inclusions tend to form clusters and remain in molten steel as large inclusions, which are harmful to the mechanical properties of steel. [24][25][26] It is generally believed that Mg treatment introduces numerous homogeneously dispersed inclusions in molten steel and the Mg-bearing inclusions show a low tendency to growth and aggregation. [27,28] The Mg-bearing inclusions have been utilized to inhibit the austenite grain growth and refine the HAZ microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that there exists a strong attraction force between REM particles which results in an agglomeration of inclusions and clusters. Bi et al 9) studied the characteristics of REM clusters in stainless steel after electrolytic extraction. An increase in the number of large sized clusters per cubic millimeter, at an expense of smaller clusters, with an increased holding time was observed.…”
Section: Formation and Growth Mechanism Of Clusters In Liquid Remallomentioning
confidence: 99%